2016
DOI: 10.4094/chnr.2016.22.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Daycare Center Teachers’ Management of Childhood Fever

Abstract: Background: Guidelines for the management of fever in children have been recently published, however "fever phobia" is still spreading. To provide information which may sustain educational interventions tailored to our population we investigated the parental and medical knowledge and management of fever in preschool children. Methods: A questionnaire was administered to a convenient sample of Italian parents and paediatricians. The questionnaire elicited information about definition and cause of fever, concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It was also identified that items that obtained the lowest difference before and after educational activity mediated by the in situ simulation were the ones related to confidence in recognizing and managing a child with a fever, that is, teachers that already showed good self-confidence levels regarding care with fever before the activity. Such finding countered with the result found by an international study that sought to identify the knowledge, anxiety and management of fever among teachers of a daycare facility 39 , which identified high levels of anxiety when faced with a feverish child 39 .…”
Section: Discussionmentioning
confidence: 69%
“…It was also identified that items that obtained the lowest difference before and after educational activity mediated by the in situ simulation were the ones related to confidence in recognizing and managing a child with a fever, that is, teachers that already showed good self-confidence levels regarding care with fever before the activity. Such finding countered with the result found by an international study that sought to identify the knowledge, anxiety and management of fever among teachers of a daycare facility 39 , which identified high levels of anxiety when faced with a feverish child 39 .…”
Section: Discussionmentioning
confidence: 69%
“…This finding contrasts with the findings of Park and Kim, who found that in Korea, teachers were concerned about dealing with fever. [ 34 ] The strong confidence of teachers in dealing with fever may refer to the fact that fever is a common illness, and therefore teachers are more familiar with treating fevers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] Regarding fever management, Park and Kim found that teachers in daycare centers in Korea have a high level of concern about fever and how to deal with it. [ 34 ]…”
Section: Literature Reviewmentioning
confidence: 99%